Pengaruh Media PowerPoint dalam pembelajaran Jarak Jauh Terhadap Aktivitas Kebugaran Jasmani Siswa - Inri Novita Dwianti; Rekha Ratri Julianti; Ega Trisna Rahayu (Peneliti.net, 2021)
This study aims to analyze and test the truth of the hypothesis regarding the Effect of Powerpoint Media in Distance Learning on the Learning Outcomes of Students' Physical Fitness Activities. This research was conducted at SMAN 1 Pedes class XI. This research was conducted using a quantitative approach and experimental methods. The population in this study amounted to 179 students in six classes. While the sample taken is cluster random sampling, so the sample size taken in this study is 35 students in one class. The instrument used in this research is a knowledge test in the form of a multiple choice question, a skill test, and a questionnaire sheet that has been validated with a reliability coefficient. The reliability in the knowledge test is 0.955, the reliability in the skills test is 0.942, and the reliability in the questionnaire sheet is 0.984. This data analysis used paired t-test assisted by SPSS. The results of this study have the following conclusions: (1) There is a significant influence in powerpoint media on students' cognitive learning outcomes from physical fitness activity material. (2) There is a significant effect of powerpoint media on students' psychomotor learning outcomes, and. (3) There is a significant effect of powerpoint media on students' attitudes.